THE EFFECT OF TECHNOLOGY RESOURCES ON COLLEGE SOPHOMORES' READING HABITS IN ILOCOS SUR POLYTECHNIC STATE COLLEGE PHILIPPINES - Leonard Manuel (Paedagogia: Jurnal Pendidikan, 2022)
Imbibing reading habits is an essential skill necessary in the acquisition of knowledge, which is highly demanding in the life of every student in the academic environment. However, as modern technological resources keep on advancing, the reading habits of students are also changing with reading on screen. This study examined the reading habits of college sophomore students as affected by technological resources. The survey instruments, distributed to 254 college sophomore students at the Ilocos Sur Polytechnic State College, allowed the respondents to assess their reading habits in terms of reading hours, reading purposes, reading content, and reading attitude, with the technological resources as their tool. The data gathered in the study was analyzed statistically using the simple frequency count and percentage, mean, and Pearson correlation. The findings revealed that the college sophomores achieved an average level in their English subjects. In addition, it was found that the technology resources were moderately adequate to be used for reading among the college sophomores. Despite this, the results still showed that college sophomore students spent 2-3 hours a day reading, primarily in preparation for their exams. In addition, they read the available reading content moderately often, and they perceive a positive attitude towards the use of technological resources for reading. Furthermore, it was revealed that there is a significant relationship between reading habits and academic achievements. The study's findings will be used to improve instructional approaches and to launch e-reading initiatives in colleges.